Pediatric thyroid abscess: an unusual late complication of COVID-19 infection - Maithani, Tripti; Gupta, Mudit; Dogra, Rishabh; Hernot, Sharad (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Coronavirus disease 2019 (COVID-19) infection in children usually presents as mild infection. There have been several reported papers of thyroid dysfunction in adults suffering from SARS-CoV-2 infection but there hasn’t been any reported case in pediatric population. We report first pediatric case of post COVID-19 thyroid abscess that developed 6 weeks post infection.